PENGGUNAAN MEDIA SOSIAL TIKTOK SEBAGAI MEDIA DAKWAH TERHADAP PENINGKATAN WAWASAN KEAGAMAAN BAGI MAHASISWA DI INSTITUT AGAMA ISLAM SAHID BOGOR - Muslikhah, Febri palupi; Noer Taufik , Rachmi Fidhara (JURNAL SAHID DA'WATII, 2022)
Indonesia is the second country to use the TikTok application in the world. The popularity of TikTok in Indonesia has become urgent in preaching through social media. The popularity of this application should be an opportunity for a Muslim to convey da'wah messages to its users. A Muslim must be able to answer the challenges of preaching in the digital era by innovating and being creative in packaging and delivering da'wah so that the message of da'wah can be accepted and is effective in changing the behavior of muslims. This study aims to find out whether the TikTok application has an impact on students' understanding of religion. This research is a quantitative study with a population of Sahid Bogor Islamic Institute students who use the TikTok social media platform. The research sample used was 39 people. Questionnaires were distributed via google form, then the data collected were analyzed using the Wilcoxon non-parametric test. The results of this study can be concluded that there is an influence from the use of the TikTok application as a da'wah media on religious insights in students at the Sahid Islamic Institute, Bogor.